(untitled) (Research, Society and Development, 2021)
The aim of the study was to describe the morphology and centesimal composition of the Nile tilapia skin and the changes that occur throughout the tanning process. Samples (middle dorsal region) were taken at the end of each stage of the tanning process, for analysis of light microscopy and scanning electron microscopy. Analyzes of the proximate composition of skins related to fish of three weight classes (500 to 600g; 601 to 700 g and 701 to 800 g) were also carried out. It was observed that the skin of the Nile tilapia has a structural pattern common to teleost fish. Through histochemical techniques, the presence of neutral carbohydrates in the mucous cells found in the superficial layer of the epidermis has been proven. The arrangement and orientation of the collagen fibers of the superficial dermis was observed, as well as of the compact dermis and the organization of the collagen fibers and of the protective insoles in the insertion of the scales. It is possible to observe the insertion of the scale in the dermal tissue, as well as its morphology. It was observed the swelling and opening of the fibrous structure at the beginning of the process, and mainly, the separation of the layers of collagen fibers throughout the process and the action of the oils of the greasing at the end of the tanning. There was a difference in the proximate composition of the skins, only in terms of lipid content. By analyzing the morphology of the skin, in relation to the organization and disposition of collagen fibers and the dermal structure during tanning, it can be inferred that the study of the histological structure of the material is fundamental for analyzing the strength of the leather.